Novel sensor material for cobalt ion detection and quantification and preparation method thereof
By fixing the PDBDP azoSchiff probe on a hexagonal mesoporous silica template, a new sensor material is formed, which solves the problem of insufficient sensitivity and selectivity of cobalt ion detection in the prior art, and achieves a high sensitivity, selectivity and reusability of cobalt ion detection effect.
Patent Information
- Application Number
- CN202411866343.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art lacks sensitivity and selectivity in cobalt ion detection, and high-precision detection requires expensive equipment and professional operation, which limits its application range.
The PDBDP azoschiff probe was used to combine with the hexagonal mesoporous silica template, and the probe was fixed on the template by direct impregnation method to form a new sensor material for cobalt ion detection and quantification.
It improves the sensitivity and selectivity of cobalt ion detection, achieves low detection limit (0.09ppb) and multiple cycles, avoids secondary pollution in the environment, and has high sensitivity, selectivity and reusability.
Smart Images

Figure CN119706850A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of environmental monitoring, and in particular to a novel sensor material for cobalt ion detection and quantification and a preparation method thereof. Background Art
[0002] Cobalt ions mainly come from the cemented carbide industry, technical equipment, chemical and pharmaceutical industries, diamond polishing, automobiles and other fields. Large doses of cobalt ions in the human body can cause cardiomyopathy, vasodilation, loss of appetite, lung disease, asthma, congestive heart failure, etc. Moreover, chronic cobalt exposure can also lead to neurotoxicological and genetic toxicological disorders, and even cancer. Therefore, the treatment of cobalt pollution and general method risk assessment, especially the risk assessment related to water samples, have received widespread attention.
[0003] In a complex water environment, the content of cobalt ions is often negligible, and the environment may be mixed with a variety of metal ions. This requires the detection technology to have excellent sensitivity and selectivity to ensure accurate identification and measurement of cobalt ions at low concentrations, while effectively distinguishing the interference of other metal ions. However, for trace cobalt, templates based on different materials have been developed one after another. The probe molecules are attached to the templates and used for multiple cycles of on-site analysis without any secondary stress on the environment. At present, some detection technologies have not yet reached the ideal high standards in terms of sensitivity and selectivity. Although some advanced technologies have made breakthroughs in sensitivity, their detection limits have not been lower than the thresholds specified by environmental and health standards, which limits their application in the actual detection of trace cobalt ions. In addition, although some high-precision instrument detection technologies have excellent performance, they rely on expensive equipment and professional operators, which not only increases economic costs, but also increases maintenance costs, thereby limiting the application of these technologies in a wider range of fields. Summary of the invention
[0004] The first object of the present invention is to provide a method for preparing a novel sensor material for cobalt ion detection and quantification, wherein a PDBDP azo Schiff probe is physically adsorbed on a hexagonal mesoporous silica template to form a novel sensor material. The template hexagonal mesoporous silica used therein has an interconnected uniform porous structure, which allows easy and rapid percolation of the analyte medium without any significant loss of performance, thereby improving the sensitivity and selectivity of cobalt ion detection.
[0005] The second object of the present invention is to provide a novel sensor material for cobalt ion detection and quantification, which is suitable for multiple cycles of on-site analysis and does not produce any secondary stress on the environment. The problem of non-reusability and secondary waste generation is solved, and the final test results also show a lower detection limit (0.09ppb). It has the advantages of high sensitivity, selectivity, reusability, etc., and can better detect and quantify cobalt ions.
[0006] The technical solution for achieving the first invention objective is a method for preparing a novel sensor material for cobalt ion detection and quantification, comprising: preparing a PDBDP azo Schiff probe and a hexagonal mesoporous silica template respectively;
[0007] The PDBDP azo Schiff probe is fixed on the surface of the hexagonal mesoporous silica template by using a direct impregnation method to prepare a new sensor material for cobalt ion detection and quantification.
[0008] Preferably, the preparation method of the PDBDP azo Schiff probe comprises:
[0009] Adding propane-1,3-diamine to anhydrous ethanol to obtain a fourth solution;
[0010] The pure BDHB product is dissolved in anhydrous ethanol to obtain a third solution;
[0011] The third solution is added to the fourth solution and stirred to prepare the PDBDP azo Schiff probe.
[0012] Preferably, the molar ratio of the third solution to the fourth solution is 1:2;
[0013] The concentration of the pure BDHB product in the third solution is 0.5 to 2 M;
[0014] The molar ratio of anhydrous ethanol to propane-1,3-diamine in the fourth solution is 1:10 to 1:15.
[0015] Preferably, the method for preparing the pure BDHB product comprises: preparing a first solution and a second solution respectively;
[0016] The first solution is prepared by dissolving 4-butylaniline in HCl, adding excess sodium nitrite under ice-cold conditions, and stirring to obtain the first solution;
[0017] The second solution is prepared by dissolving 2-hydroxybenzaldehyde in a NaOH solution and keeping the solution under ice-cold conditions to obtain a second solution;
[0018] The second solution is added to the first solution, the reaction pH is maintained at 8-9, stirring and washing are performed to obtain a pure BDHB product.
[0019] Preferably, the molar ratio of the first solution to the second solution is 0.78:1;
[0020] The molar ratio of 4-butylaniline to HCl in the first solution is 1:2 to 2:1;
[0021] The molar ratio of 2-hydroxybenzaldehyde to NaOH solution in the second solution is 1:2 to 2:1;
[0022] The concentration of the NaOH solution is 2.75-2.8M.
[0023] Preferably, the preparation method of the hexagonal mesoporous silica template comprises: dispersing a block copolymer of polyethylene glycol and polypropylene glycol and sodium dodecyl sulfate in deionized water, adding HCl and tetraethyl orthosilicate in sequence, reacting at 30° C., then reacting in an autoclave, filtering, washing, drying, and calcining to obtain a hexagonal mesoporous silica template.
[0024] Preferably, the mass ratio of the block copolymer of polyethylene glycol and polypropylene glycol, sodium dodecyl sulfate, HCl, and tetraethyl orthosilicate is 8:1:192:20.
[0025] Preferably, the direct impregnation method comprises dissolving the PDBDP azo Schiff probe in an anhydrous ethanol solution, and then impregnating the hexagonal mesoporous silica template therein for equilibrium.
[0026] Preferably, the mass ratio of the PDBDP azo Schiff probe, the anhydrous ethanol solution, and the hexagonal mesoporous silica template is 4:20:1.
[0027] The technical solution for achieving the second invention objective is a new sensor material for cobalt ion detection and quantification.
[0028] Beneficial effects of the above technical solution:
[0029] The invention provides a novel sensor material for cobalt ion detection and quantification, wherein a PDBDP azo Schiff probe is physically adsorbed on a hexagonal mesoporous silica template to form a novel sensor material. The sensor material is used to detect cobalt ions in an aqueous environment, and the purpose is to form a complex with the cobalt ions at trace concentrations. The template hexagonal mesoporous silica used has an interconnected uniform porous structure, which allows easy and rapid percolation of the analyte medium without any significant loss of performance, thereby improving the sensitivity and selectivity of cobalt ion detection.
[0030] The preparation method provided by the present invention is to adhere the PDBDP azo Schiff probe to a hexagonal mesoporous silica template, and the method is suitable for multiple cycles of on-site analysis, and does not produce any secondary stress on the environment. The problems of non-reusability and secondary waste generation are solved, and the final test results also show a lower detection limit (0.09ppb). Therefore, the present invention circumvents the inherent problems of the prior art, has the advantages of high sensitivity, selectivity, reusability, etc., and can better detect and quantify cobalt ions. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without creative work.
[0032] Figure 1 A schematic diagram of the synthesis route for preparing a PDBDP probe from a novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0033] Figure 2 A 50 μm scanning electron microscope (SEM) image of the novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0034] Figure 3 20 μm scanning electron microscope (SEM) image of the novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0035] Figure 4 Transmission electron microscopy (TEM) image of the novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0036] Figure 5 A low-angle X-ray diffraction (Low-angle XRD) spectrum of a novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0037] Figure 6 Wide-angle X-ray diffraction (Wide-angle XRD) spectrum of the new sensor material for cobalt ion detection and quantification provided in Example 2;
[0038] Figure 7 This is a X-ray photoelectron spectroscopy (XPS) diagram of a new sensor material for cobalt ion detection and quantification provided in Example 2;
[0039] Figure 8 Energy dispersive spectroscopy (EDS) diagram of a novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0040] Fig. 9 The novel sensor material for cobalt ion detection and quantification provided in Example 2 is for Co 2+ Ion selectivity results graph;
[0041] Fig.10 A graph showing the reusability of the novel sensor material for cobalt ion detection and quantification provided in Example 2;
[0042] Fig.11 This is a graph showing the durability results of the new sensor material for cobalt ion detection and quantification provided in Example 2. DETAILED DESCRIPTION
[0043] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0044] Examples of the embodiments are shown in the accompanying drawings, wherein the same or similar symbols throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present invention, and should not be construed as limiting the present invention.
[0045] Embodiment 1
[0046] The novel sensor material for cobalt ion detection and quantification provided by the present invention comprises a PDBDP azo Schiff probe and a hexagonal mesoporous silica template. The PDBDP azo Schiff probe is directly adsorbed and fixed on the surface of the silica template by a direct impregnation method to synthesize a novel sensor material for cobalt ion detection and quantification, and the novel sensor material is characterized in that it contains Co 2+ Solid-state sensor materials based on complex materials for Co in water environments 2+ Detection and quantification of. Specifically include the following steps:
[0047] (I) Preparation of PDBDP azo Schiff probe
[0048] Prepare the first solution: dissolve 1.0 g of 4-butylaniline in 2 mL of 6 M HCl, add excess sodium nitrite (NaNO2) under ice-cooling conditions, and continuously stir for 30 min to obtain the first solution.
[0049] Preparation of the second solution: 1.05 g of 2-hydroxybenzaldehyde was dissolved in 6 mL of 2.75 M NaOH solution and kept under ice-cooling conditions for 3 hours to obtain a second solution.
[0050] Preparation of pure BDHB product: slowly add the second solution into the first solution, maintain the reaction pH at 8.0-9.0, stir for 12 hours to obtain the product (Z)-5-(4-hydroxyphenyl)-2-methyl-N-(2-methyl)-2-methyl-N-(3-methyl)-2-(((4-butylphenyl)diazine)2-hydroxybenzaldehyde (BDHB), and purify it by washing with deionized water and hexane to obtain pure BDHB product.
[0051] Prepare the third solution: dissolve 2.05 g of BDHB in 15 mL of anhydrous ethanol to obtain the third solution.
[0052] Prepare the fourth solution: add 1.0 g of propane-1,3-diamine to 8 mL of anhydrous ethanol to obtain the fourth solution.
[0053] The third solution was added to the fourth solution and stirred at room temperature for 24 hours to prepare the PDBDP azo Schiff probe.
[0054] (II) Preparation of hexagonal mesoporous silica template
[0055] 1.0 g of a block copolymer of polyethylene glycol and polypropylene glycol (F127) and 0.125 g of sodium dodecyl sulfate (SDS) were uniformly dispersed in 30.0 g of water, 24.0 g of 1 M HCl was added thereto at room temperature, and the mixture was continuously stirred, and then 2.5 g of tetraethyl orthosilicate (TEOS) was added thereto to obtain a fifth solution; the fifth solution was placed in a hot air oven at 30° C. for 24 h; then the solution was transferred and sealed to a polytetrafluoroethylene (Teflon)-coated autoclave, heated at 100° C. for 24 h, filtered to obtain a white solid, washed, dried at 40° C. for 6 h, and then calcined at 550° C. at a heating rate of 2° C. / min for 5 h to obtain a hexagonal mesoporous silica template;
[0056] (III) Probe Fixation
[0057] The PDBDP azo Schiff probe was directly adsorbed and fixed on the surface of the hexagonal mesoporous silica template by direct impregnation method.
[0058] The PDBDP azo Schiff probe was dissolved in 25 mL of anhydrous ethanol, and then 1.0 g of hexagonal mesoporous silica template was immersed in it. After equilibration for 6 h, the final new sensor material was obtained. A new sensor material for cobalt ion detection and quantification.
[0059] Embodiment 2
[0060] like Figure 1 The figure shows a schematic diagram of the synthesis route of the novel sensor material for cobalt ion detection and quantification provided in the second embodiment for preparing the PDBDP probe, which specifically includes the following steps:
[0061] (I) Preparation of PDBDP azo Schiff probe
[0062] Prepare the first solution: dissolve 1.0 g of 4-butylaniline in 1 mL of 6 M HCl, add excess sodium nitrite (NaNO2) under ice-cold conditions, and stir continuously for 30 min to obtain the first solution.
[0063] Preparation of the second solution: 1.05 g of 2-hydroxybenzaldehyde was dissolved in 3 mL of 2.775 M NaOH solution and kept under ice-cooling conditions for 3 hours to obtain a second solution.
[0064] Preparation of pure BDHB product: slowly add the second solution into the first solution, maintain the reaction pH at 8.0-9.0, stir for 12 hours to obtain the product (Z)-5-(4-hydroxyphenyl)-2-methyl-N-(2-methyl)-2-methyl-N-(3-methyl)-2-(((4-butylphenyl)diazine)2-hydroxybenzaldehyde (BDHB), and purify it by washing with deionized water and hexane to obtain pure BDHB product.
[0065] Preparation of the third solution: 2.05 g of BDHB was dissolved in 6 mL of anhydrous ethanol to obtain the third solution.
[0066] Prepare the fourth solution: add 1.0 g of propane-1,3-diamine into 10 mL of anhydrous ethanol to obtain the fourth solution.
[0067] The third solution was added to the fourth solution and stirred at room temperature for 24 hours to prepare the PDBDP azo Schiff probe.
[0068] (II) Preparation of hexagonal mesoporous silica template
[0069] 1.0 g of a block copolymer of polyethylene glycol and polypropylene glycol (F127) and 0.125 g of sodium dodecyl sulfate (SDS) were uniformly dispersed in 30.0 g of water, 24.0 g of 1 M HCl was added thereto at room temperature, and the mixture was continuously stirred, and then 2.5 g of tetraethyl orthosilicate (TEOS) was added thereto to obtain a fifth solution; the fifth solution was placed in a hot air oven at 30° C. for 24 h; then the solution was transferred and sealed to a polytetrafluoroethylene (Teflon)-coated autoclave, heated at 100° C. for 24 h, filtered to obtain a white solid, washed, dried at 40° C. for 6 h, and then calcined at 550° C. at a heating rate of 2° C. / min for 5 h to obtain a hexagonal mesoporous silica template;
[0070] (III) Probe Fixation
[0071] The PDBDP azo Schiff probe was directly adsorbed and fixed on the surface of the hexagonal mesoporous silica template by direct impregnation method.
[0072] The PDBDP azo Schiff probe was dissolved in 25 mL of anhydrous ethanol, and then 1.0 g of hexagonal mesoporous silica template was immersed in it. After equilibration for 6 h, the final new sensor material was obtained. A new sensor material for cobalt ion detection and quantification.
[0073] Embodiment 3
[0074] (I) Preparation of PDBDP azo Schiff probe
[0075] Prepare the first solution: dissolve 1.0 g of 4-butylaniline in 0.5 mL of 6M HCl, add excess sodium nitrite (NaNO2) under ice-cooling conditions, and stir continuously for 30 min to obtain the first solution.
[0076] Preparation of the second solution: 1.05 g of 2-hydroxybenzaldehyde was dissolved in 1 mL of 2.8 M NaOH solution and kept under ice-cooling conditions for 3 hours to obtain a second solution.
[0077] Preparation of pure BDHB product: slowly add the second solution into the first solution, maintain the reaction pH at 8.0-9.0, stir for 12 hours to obtain the product (Z)-5-(4-hydroxyphenyl)-2-methyl-N-(2-methyl)-2-methyl-N-(3-methyl)-2-(((4-butylphenyl)diazine)2-hydroxybenzaldehyde (BDHB), and purify it by washing with deionized water and hexane to obtain pure BDHB product.
[0078] Preparation of the third solution: 2.05 g of BDHB was dissolved in 3.6 mL of anhydrous ethanol to obtain the third solution.
[0079] Prepare the fourth solution: add 1.0 g of propane-1,3-diamine into 12 mL of anhydrous ethanol to obtain the fourth solution.
[0080] The third solution was added to the fourth solution and stirred at room temperature for 24 hours to prepare the PDBDP azo Schiff probe.
[0081] (II) Preparation of hexagonal mesoporous silica template
[0082] 1.0 g of a block copolymer of polyethylene glycol and polypropylene glycol (F127) and 0.125 g of sodium dodecyl sulfate (SDS) were uniformly dispersed in 30.0 g of water, 24.0 g of 1 M HCl was added thereto at room temperature, and the mixture was continuously stirred, and then 2.5 g of tetraethyl orthosilicate (TEOS) was added thereto to obtain a fifth solution; the fifth solution was placed in a hot air oven at 30° C. for 24 h; then the solution was transferred and sealed to a polytetrafluoroethylene (Teflon)-coated autoclave, heated at 100° C. for 24 h, filtered to obtain a white solid, washed, dried at 40° C. for 6 h, and then calcined at 550° C. at a heating rate of 2° C. / min for 5 h to obtain a hexagonal mesoporous silica template;
[0083] (III) Probe Fixation
[0084] The PDBDP azo Schiff probe was directly adsorbed and fixed on the surface of the hexagonal mesoporous silica template by direct impregnation method.
[0085] The PDBDP azo Schiff probe was dissolved in 25 mL of anhydrous ethanol, and then 1.0 g of hexagonal mesoporous silica template was immersed in it. After equilibration for 6 h, the final new sensor material was obtained. A new sensor material for cobalt ion detection and quantification.
[0086] Performance Evaluation
[0087] The performance of the new sensor material for cobalt ion detection and quantification provided in Example 2 was tested. Figures 2 to 8 It can be seen that the results of SEM, TEM, XRD, XPS, and EDS characterization. The new sensor material provided by the present invention, wherein the SEM image confirms the uniform pore structure on the surface of the material and the formation of a single piece. The TEM image can be observed to be isotropic and gradually densified sol condensation accompanied by the triggered two-phase gel to form porous channels, which can make the fluidity of the liquid analyte faster, thereby producing a fast response dynamics of the sensor medium. The low-angle XRD results show that the hexagonal porous nature of the material has not changed. The wide-angle XRD results show the amorphous nature of the material. The XPS image reveals the presence of Si, O, N, C and Co elements in the sensor material, confirming the successful incorporation of PDBDP in the silica monolithic matrix material and its reaction with Co. 2+ The EDS graph also reveals the presence of Si, O, N, C and Co elements, which is consistent with the results of the elemental composition analyzed by XPS.
[0088] The novel sensor material for cobalt ion detection and quantification provided in Example 2 is used for Co 2+ The selectivity of ions was tested, and the results were as follows Fig. 9 As shown. It can be seen that the new sensor material has a good effect on Co 2+The ions have obvious selectivity, which proves that the new sensor material provided by the present invention can be used for cobalt ion detection and quantification.
[0089] The repeatability and practicability of the novel sensor material for cobalt ion detection and quantification provided in Example 2 were tested, and the results were as follows: Fig.10 As shown in the figure, the performance of the new sensor material does not decrease significantly with the increase of the number of cycles. It can be seen that it has excellent reusability.
[0090] The durability of the novel sensor material for cobalt ion detection and quantification provided in Example 2 was tested, and the results were as follows: Fig.11 As shown. It can be seen that over time, the stability of the new sensor material provided by the present invention has not significantly decreased. The performance is relatively stable.
[0091] In summary, the novel sensor material for cobalt ion detection and quantification provided by the present invention is suitable for multiple cycles of on-site analysis and does not produce any secondary stress on the environment. The problem of non-reusability and secondary waste generation is solved, and the final test results also show a lower detection limit (0.09 ppb) and quantification limit (0.31 ppb), reusability (12 times), and long-term durability (14 months). The preparation method of the present invention allows the complexation site to specifically allow only Co 2+ The synergistic effect of the fine-tuned mesoporous silica monolith and the probe enables the sensor system to selectively capture Co even at extreme matrix ion concentrations. 2+ Therefore, the present invention avoids the inherent problems of the prior art, has the advantages of high sensitivity, selectivity, reusability, etc., and can better detect and quantify cobalt ions.
[0092] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some of the technical features can be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing a novel sensor material for cobalt ion detection and quantification, characterized in that: include: The PDBDP azo Schiff probe and the hexagonal mesoporous silica template were prepared respectively; The PDBDP azo Schiff probe is fixed on the surface of the hexagonal mesoporous silica template by using a direct impregnation method to prepare a new sensor material for cobalt ion detection and quantification.
2. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 1, characterized in that: The preparation method of the PDBDP azo Schiff probe comprises: Adding propane-1,3-diamine to anhydrous ethanol to obtain a fourth solution; The pure BDHB product is dissolved in anhydrous ethanol to obtain a third solution; The third solution is added to the fourth solution, and stirred to prepare the PDBDP azo Schiff probe.
3. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 2, characterized in that: The molar ratio of the third solution to the fourth solution is 1:2; The concentration of the pure BDHB product in the third solution is 0.5 to 2 M; The molar ratio of anhydrous ethanol to propane-1,3-diamine in the fourth solution is 1:10 to 1:
15.
4. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 2, characterized in that: The method for preparing the pure BDHB product comprises: preparing a first solution and a second solution respectively; The first solution is prepared by dissolving 4-butylaniline in HCl, adding excess sodium nitrite under ice-cold conditions, and stirring to obtain the first solution; The second solution is prepared by dissolving 2-hydroxybenzaldehyde in a NaOH solution and keeping the solution under ice-cold conditions to obtain a second solution; The second solution is added to the first solution, the reaction pH is maintained at 8-9, stirring and washing are performed to obtain a pure BDHB product.
5. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 4, characterized in that: The molar ratio of the first solution to the second solution is 0.78:1; The molar ratio of 4-butylaniline to HCl in the first solution is 1:2 to 2:1; The molar ratio of 2-hydroxybenzaldehyde to NaOH solution in the second solution is 1:2 to 2:1; The concentration of the NaOH solution is 2.75-2.8M.
6. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 1, characterized in that: The preparation method of the hexagonal mesoporous silica template comprises: dispersing a block copolymer of polyethylene glycol and polypropylene glycol and sodium dodecyl sulfate in deionized water, adding HCl and tetraethyl orthosilicate in sequence, reacting at 30° C., then reacting in an autoclave, filtering, washing, drying, and calcining to obtain the hexagonal mesoporous silica template.
7. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 6, characterized in that: The mass ratio of the block copolymer of polyethylene glycol and polypropylene glycol, sodium dodecyl sulfate, HCl and tetraethyl orthosilicate is 8:1:192:
20.
8. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 1, characterized in that: The direct impregnation method comprises dissolving the PDBDP azo Schiff probe in an anhydrous ethanol solution, then impregnating the hexagonal mesoporous silica template therein, and balancing.
9. The method for preparing the novel sensor material for cobalt ion detection and quantification according to claim 8, characterized in that: The mass ratio of the PDBDP azo Schiff probe, the anhydrous ethanol solution, and the hexagonal mesoporous silica template is 4:20:
1.
10. A novel sensor material for cobalt ion detection and quantification prepared by the preparation method according to any one of claims 1 to 9.